COMPARATIVE GROSS ANATOMICAL STUDIES ON THE FREE CAUDAL VERTEBRAE AND PYGOSTYLE OF KITE, CROW AND PIGEON USING DERMESTID BEETLE TECHNIQUE (Applied Biological Research, 2023)
The present study was aimed to study the gross anatomy of free caudal  vertebrae and pygostyle of kite, pigeon and crow and compare individual  vertebrae within and between the species. Twelve dead adult birds from  each specie were used. The collected bones were prepared for study as per Dermestid Beetle Decomposition technique. The number of free caudal  vertebrae in kite, pigeon and crow were 7, 6 and 6, respectively. The  presence of bifid dorsal & ventral spine, and a distinct cranial articular  process in initial segments was characteristic in kite. In pigeon, ventral  spine was absent in 1st three caudal vertebrae while 6th caudal vertebra was  ygostyle. In crow, ventral spine was absent in 1st two  caudal vertebrae while in rest vertebrae it was tuberous. The length of  transverse process in all the species was initially less, increased in middle  region and reduced towards end. The last free caudal vertebra in pigeon  lacked transverse process. The pygostyle was trapezoid in kite, triangular in  crow and roughly quadrilateral in pigeon. The study revealed significant  differences in caudal vertebrae within and between the species. The  presence of cranaial articular processes and tuberculous structures  suggested that free caudal vertebrae in kite were well-developed for strong  catch hold to the skeletal muscles for better hunting. The pygostyle and free  caudal vertebrae were more closely related in kite and crow than in pigeon.
Keywords: Caudal vertebrae; crow; kite; pigeon; pygostyle